HYDROCARBON POTENTIAL OF THE SOUTH-EASTERN UNDERTHRUST PART OF PRECARPATHIAN’S FOREDEEP OUTER ZONE - Михайлів, Ірина Романівна; Мазур, Анна Павлівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The development of the hydrocarbon potential of Cretaceous sediments of Outer zone can make a significant contribution in the energy supplies of Ukraine’s own raw materials. Well-grounded prediction increases of oil and gas prospecting success. In this regard, it is important to justify the hydrocarbon potential of Cretaceous sediments for criterium complex traits, which include the establishment of favorable structural and tectonic conditions for the formation and preservation of oil and gas.